Dual–Functional‐Polymer Dopant–Passivant Boosted Electron Transport Layer for High‐Performance Inverted Perovskite Solar Cells. Issue 7 (12th May 2021) - Xu, Rongguo; Wang, Zhenfeng; Xu, Wenzhan; Xu, Xiuwen; Wang, Jian; Hu, Zhicheng; Li, Yu; Wang, Gaopeng; Cai, Wanqing; Zheng, Shizhao; Wei, Guodan; Huang, Fei; et al.
Abstract : Herein, the use of the polymer poly([ N, N ′‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene)) (PNDI‐2T) as both a dopant in the [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) electron transport layer (ETL) of inverted perovskite solar cells (PSCs) and a surface passivant on the perovskite layer is reported. The PNDI‐2T doping is found to be crucial for improving the homogeneity of the ETL film with complete surface coverage, enhancing the electron mobility of the ETL, and promoting the energy level match between the perovskite and ETL, thereby significantly facilitating electron transport in the PSC devices. Furthermore, as a passivant, the PNDI‐2T in the ETL tends to pin on the top surface of the perovskite layer via PbS coordination. The surface passivation is also beneficial for the suppression of ion migration and diffusion of metal species from the electrodes. In consequence, PSCs with the PCBM:PNDI‐2T ETL reached an efficiency of 21.13% and retain 90% of their original performance after 860 h light soaking. This work will inspire new efforts to take advantage of multifunctional ETLs as a simple and effective method to enhance the performance and long‐term stability of PSCs. Abstract : A dual‐functional polymer is introduced into a [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) layer to simultaneously modify the PCBM electron transport layer (ETL) and passivate the surface defects in the perovskite. The hybrid ETL exhibits excellent electronic properties and the ability to suppress the ion migration in perovskite solar cells, leading to a high power conversion efficiency of 21.13% and long‐term stability.